Pelatihan Pemanfaatan Limbah Baglog Jamur Tiram Menjadi Pupuk Multi Fungsi di Kota Palangka Raya: Training on Utilization of Oyster Mushroom Baglog Waste into Multi-Function Fertilizer in Palangka Raya - Saraswati, Dewi; Nion, Yanetri Asi; Mulyani, Rahmawati Budi; Kamillah, Kamillah; Djaya, Adrianson Agus; Sari, Siniy Kumala; Wardhana, Vinsen Willi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
From July to September 2024, a community service team from the Agrotechnology Study Program, Faculty of Agriculture, University of Palangka Raya, together with partners, conducted training on utilizing oyster mushroom baglog waste into multi-function fertilizer for mushroom farmers in Palangka Raya. The first partner is the Indonesian Phytopathology Association Central Kalimantan Regional Commissariat (PFI Komda Kalteng) and the second is mushroom farmers in Palangka Raya. The methods used include preparation, counseling, mentoring, and demonstrations, as well as training in Trichoderma propagation, making Trichocompost, compost packaging, and using compost as a planting media. Additionally, demonstration plots are made using Trichocompost. The mushroom farmers have succeeded in mastering the technique of making Trichocompost from oyster mushroom baglog waste. This innovation not only reduces environmental waste but also makes oyster mushroom cultivation more sustainable. Waste that is usually thrown away or only used as direct fertilizer is now processed into a multifunction fertilizer that can stimulate plant growth and increase plant resistance to disease that proven by a demonstration plot of chili cultivation using Trichokompos. This processing process not only increases the efficiency of natural resource use but also provides added value to waste and increases mushroom farmers' income.